Development of an Android-based Stroke Prevention Application - Rizani, Khairir; Sofia, Norlaila; Fratama, Ferry Fadli; Imanuddin, M. Rizki (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Stroke remains a significant public health problem in Indonesia, with a prevalence of 8.3 per 1,000 population and a significant contribution to disability and mortality. Limited community health literacy and underutilization of digital health media indicate the need for accessible technology-based stroke prevention interventions. This study aimed to develop and validate a community-oriented Android-based application for stroke prevention using an ADDIE-based Research and Development framework. This study contributes a validated mobile health intervention for community stroke prevention and a replicable development model adaptable to other non-communicable disease prevention programs. The development process included application design, feature and database construction, internal testing, expert validation, and small-group usability testing. experts. Media validation involved three instructional technology experts. A small-group usability test was conducted with 15 adult community members in Banjar Regency, selected through convenience sampling. Data were analyzed using descriptive statistics and feasibility classification. The application obtained a mean score of 4.7 from material experts and 4.9 from media experts, indicating a “Highly Feasible” classification. Usability testing showed an overall mean score of 16.8 out of 20, reflecting strong user acceptance. This study is limited by its small sample size and short-term evaluation without behavioral or clinical outcome assessment. Nevertheless, the application shows potential as a digital health education tool to improve stroke prevention literacy and support community-based prevention programs and national digital health strategies.